2010
DOI: 10.1007/s00442-010-1564-x
|View full text |Cite
|
Sign up to set email alerts
|

Differential habitat use and antipredator response of juvenile roach (Rutilus rutilus) to olfactory and visual cues from multiple predators

Abstract: The indirect, behavioral effects of predation and predator-predator interactions can significantly alter the trophic ecology of many communities. In numerous instances, the strength of these effects may be determined by the ability of prey to identify predation risk through predator-specific cues and respond accordingly to avoid capture. We exposed juvenile roach (Rutilus rutilus), a common forage fish in many brackish and freshwater environments, to vision and/or olfactory cues from two predators with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 66 publications
(77 reference statements)
2
59
0
1
Order By: Relevance
“…Recent work has highlighted emergence from structurally complex habitat as a significant predation gauntlet, even more so than the separate effects of using matrix habitat, following from the concentration of predators along habitat boundaries (sensu Martin et al 2010). Therefore, the ability of fishes to connect/colonize patches within a fragmented landscape may be largely regulated by rates of emergence from seagrass, which is well-defined at our mesocosm scale.…”
Section: Accepted Articlementioning
confidence: 97%
“…Recent work has highlighted emergence from structurally complex habitat as a significant predation gauntlet, even more so than the separate effects of using matrix habitat, following from the concentration of predators along habitat boundaries (sensu Martin et al 2010). Therefore, the ability of fishes to connect/colonize patches within a fragmented landscape may be largely regulated by rates of emergence from seagrass, which is well-defined at our mesocosm scale.…”
Section: Accepted Articlementioning
confidence: 97%
“…The experimental design was substitutive; thus, the number of Nile tilapia and the total numbers of each species were the same in each group. All treatments were replicated three times (Griffen, 2006;Martin et al, 2010b). There were 60 individuals in each mesocosm and 20 fishes in each ecological system.…”
Section: > Experiments 2: Laboratory Experimentsmentioning
confidence: 99%
“…However, use of the PVC tubes by bullies would also limit their ability to use visual cues. Other studies have shown a preference for more open habitat with a larger visual field when there is a perceived predation threat (see Rilov et al 2007), and only moving to more structured habitat when presented with a direct visual cue (see Martin et al 2010). Another interesting finding was that the overall proportion of times bullies were observed using cover between the two treatments was only about 0.1% different, possibly reflecting a cumulative diel use of cover with significant changes in periodicity only.…”
Section: Discussionmentioning
confidence: 89%
“…To supplement vision, fish may utilize olfactory cues for predator detection and avoidance (e.g., Brown et al 2000;Hartman and Abrahams 2000). Recognition of predators through chemoreception and resulting behavioural responses are well documented (e.g., Kelley and Magurran 2003;Martin et al 2010). Other cues used by fish include social, electrical and mechanosensory (Montgomery et al 1995;Hanika and Kramer 2000;Brown and Laland 2003).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation